Lipids in Liver Failure Syndromes: A Focus on Eicosanoids, Specialized Pro-Resolving Lipid Mediators and Lysophospholipids - Artru, Florent; McPhail, Mark J. W.; Triantafyllou, Evangelos; Trovato, Francesca Maria (Frontiers in Immunology, 2022)
Lipids are organic compounds insoluble in water with a variety of metabolic and non-metabolic functions. They not only represent an efficient energy substrate but can also act as key inflammatory and anti-inflammatory molecules as part of a network of soluble mediators at the interface of metabolism and the immune system. The role of endogenous bioactive lipid mediators has been demonstrated in several inflammatory diseases (rheumatoid arthritis, inflammatory bowel disease, atherosclerosis, cancer). The liver is unique in providing balanced immunotolerance to the exposure of bacterial components from the gut transiting through the portal vein and the lymphatic system. This balance is abruptly deranged in liver failure syndromes such as acute liver failure and acute-on-chronic liver failure. In these syndromes, researchers have recently focused on bioactive lipid mediators by global metabonomic profiling and uncovered the pivotal role of these mediators in the immune dysfunction observed in liver failure syndromes explaining the high occurrence of sepsis and subsequent organ failure. Among endogenous bioactive lipids, the mechanistic actions of three classes (eicosanoids, pro-resolving lipid mediators and lysophospholipids) in the pathophysiological modulation of liver failure syndromes will be the topic of this narrative review. Furthermore, the therapeutic potential of lipid-immune pathways will be described.